Entrepreneurship performance of Vietnam - Thi Thu Ha, Nguyen; Ba Hoa, Lam (Serbian Journal of Management, 2022)
The study aims to measure entrepreneurship performance of Vietnam in comparison to Asian countries by applying the Global Entrepreneurship Development Index (GEDI) and then employed the Penalty for Bottleneck (PFB) methodology to allocate priority policies for the improvement of entrepreneurship performance in Vietnam. Specifically, the GEDI consisting of three sub-indices: Entrepreneurial Attitudes, Entrepreneurial Abilities and Entrepreneurial Aspiration, which are divided into 14 pillars and further subdivided into 28 variables, is used to identify the best and worst performing variables of the GEDI in Vietnam in comparison to Asian countries. Then the PFB methodology provides a more realistic analysis, aiming to discover bottle-neck factors, which are poorly performing system components before suggesting recommendations to achieve the greatest improvement of entrepreneurship performance in Vietnam. The results indicate that ten bottlenecks of 14 pillars are poorly performing with very low scores in Vietnam, in which the top priority policy is given for five pillars, including Risk acceptance, Opportunity perception, Internationalization, Technology absorption and Process innovation.
Keywords: bottleneck; entrepreneurship performance; the Global Entrepreneurship Development Index; the Penalty for Bottleneck